Redefining Tourism Governance in Raja Ampat: Sustainable Development Plus, Governance Index and Android Based App Open Access - Marlon Arthur Huwae; Fikri Muhamad Hanif; Klasina Rumbekwan (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2018)
To develop tourism sustainably in an emerging tourism destination especially Raja Ampat, there is a need to manage regional identity and develop governance arrangements that bond tourism development and community together. The government as a key initiator of community empowerment, needs to ensure its governance arrangements are efficient. This paper develops a framework to measure the effectiveness of regional governance for sustainable tourism development based on two main elements: sustainable development plus and tourism governance. Sustainable development plus consists of two core named internal and external layers. The tourism governance is then measured by data triangulation, and analysis. The result of the analysis is articulated into tourism governance index and management strategy based on Boston Consulting Group Matrix. This framework which later transformed into governance matrix can be used to set up governance index to help the government improve the governance performance. The android based app open access is also developed to bring policy making process closer to the community and global sphere.